Structural behaviour of hollow core reinforced concrete (HCRC) short column under static load / Mohd Samsudin Abdul Hamid and Muhammad Aidil Nordin - Abdul Hamid, Mohd Samsudin; Nordin, Muhammad Aidil (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
The high strength-to-weight and low self-weight ratio of Hollow Core Reinforced Concrete (HCRC) short columns have made them a popular choice for application in construction. Nevertheless, little is known about how HCRC short columns behave when subjected to static loads. This is because HCRC short columns are a relatively recent type of structural member, and there has been little research into how well they behave when subjected to static loads. Given that HCRC short columns are made of composite material, it poses one of the difficulties in understanding their behaviour when subjected to static load. The complex relationship between the steel reinforcement and concrete core potentially affects the column’s ability to support loads and failure more. The purpose of this research is to evaluate their failure mechanisms and assess the structural performance under static load. Finite element models with different configuration are modelled which can simulate the complex behaviour of reinforced concrete structures under static load. This study found that Square Hollow Core (SHC) and Circular Hollow Core (CHC) are known as the most affected columns in terms of displacement compared to Rectangular Hollow Core (RHC). Stress was critically found at the top section of the column and it reduced towards lower section. The finding is able to optimize load-bearing efficiency, reduce material usage, enhance stability, improve resistance, and be proposed as modern structural applications.